TRADITION AND ITS INFLUENCE ON MODERN DERMATOLOGY - Александрук, О. Д.; Ткач, В. Є. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Overview of contemporary ideas on eczema as disease and approaches to classify it in world dermatology were given. Examples of classifications based on different principles were given as well as compared with national approach to diagnose eczema. Historically dependent significant difference of national way to classify eczema in comparison to western analogues was shown that makes some inconveniences to national specialists.